Mechanisms of pro-arrhythmic abnormalities in ventricular repolarisation and anti-arrhythmic therapies in human hypertrophic cardiomyopathy. (July 2016) - Passini, Elisa; Mincholé, Ana; Coppini, Raffaele; Cerbai, Elisabetta; Rodriguez, Blanca; Severi, Stefano; Bueno-Orovio, Alfonso
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is a cause of sudden arrhythmic death, but the understanding of its pro-arrhythmic mechanisms and an effective pharmacological treatment are lacking. HCM electrophysiological remodelling includes both increased inward and reduced outward currents, but their role in promoting repolarisation abnormalities remains unknown. The goal of this study is to identify key ionic mechanisms driving repolarisation abnormalities in human HCM, and to evaluate anti-arrhythmic effects of single and multichannel inward current blocks. Methods: Experimental ionic current, action potential (AP) and Ca 2 + -transient (CaT) recordings were used to construct populations of human non-diseased and HCM AP models (n = 9118), accounting for inter-subject variability. Simulations were conducted for several degrees of selective and combined inward current block. Results: Simulated HCM cardiomyocytes exhibited prolonged AP and CaT, diastolic Ca 2 + overload and decreased CaT amplitude, in agreement with experiments. Repolarisation abnormalities in HCM models were consistently driven by L-type Ca 2 + current (ICaL ) re-activation, and ICaL block was the most effective intervention to normalise repolarisation and diastolic Ca 2 +, but compromised CaT amplitude. Late Na + current (INaL ) block partially abolished repolarisation abnormalities, with small impact on CaT. Na + /Ca 2 + exchanger (INCX ) block effectively restored repolarisation and CaT amplitude, but increased Ca 2 + overload. Multichannel block increased efficacy in normalising repolarisation, AP biomarkers and CaT amplitude compared to selective block. Conclusions: Experimentally-calibrated populations of human AP models identify ICaL re-activation as the key mechanism for repolarisation abnormalities in HCM, and combined INCX, INaL and ICaL block as effective anti-arrhythmic therapies also able to partially reverse the HCM electrophysiological phenotype. Highlights: In silico populations of human ventricular AP models recapitulate the HCM phenotype. HCM remodelling enlarges variability and promotes repolarisation abnormalities (EADs). ICaL re-activation underlies repolarisation abnormalities in human HCM. Selective inward current blocks suppress EADs and partially reverse the HCM phenotype. INCX block improves the efficacy of INaL and ICaL selective blocks in HCM.